Imaginary Wor(l)ds: A Creative Methodology to Explore Future Imaginaries of Climate Change-Induced (Im)mobilities - Giacomelli, Elena; Peca, Stefania; Musarò, Pierluigi; Parmiggiani, Paola (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2025)
In recent decades, migration and climate change have emerged as two of the most urgent moral and political challenges confronting the twenty-first century. Predominantly portrayed in mainstream media and political discourse within the Global North as exceptional and extraordinary phenomena, the intersection of migration and climate change is increasingly framed through securitization narratives. This article critically examines the social imaginaries surrounding climate change-induced (im)mobilities, with particular attention to the extent to which these narratives are articulated in terms of justice. Empirically, the study draws on a corpus of 78 fictional stories produced by academics, media professionals, and activists, collected via the “Imaginary wor(l)ds” method during participatory seminars. This creative, practice-led methodology invited participants to collaboratively imagine and narrate future scenarios of climate (im)mobilities, aiming to bridge academic research with public engagement and foster new imaginaries through collective storytelling. The approach is grounded in the recognition that creative writing can disrupt dominant knowledge systems and open discursive space for alternative interpretations. The aim was to reflect on whether an effective collaboration between science, media, and activism might generate counter-narratives for climate (im)mobilities. The stories were analyzed using a typology of frames—victims, security threats, adaptive agents, and political subjects—to identify recurring patterns and the extent to which justice-oriented perspectives emerge. By integrating insights from mobility justice and climate justice frameworks, the study opens a path on how creative, participatory methodologies can reframe public and policy discourses on climate migration, foregrounding justice-oriented approaches over securitized paradigms. The article concludes by underscoring the importance of decolonial and intersectional perspectives in shaping future imaginaries and informing equitable policy responses to global climate (im)mobilities.